2009
DOI: 10.1590/s0004-282x2009000600037
|View full text |Cite
|
Sign up to set email alerts
|

The motor evoked potential in aids and HAM/TSP State of the evidence

Abstract: -Objective: We aimed to better understand the involvement of the corticospinal tract, assessed by non-invasive transcranial stimulation, in order to determine the actual involvement of the motor system in patients with HAM/TSP and AIDS. Method: An exhaustive MEDLINE search for the period of 1985 to 2008 for all articles cross-referenced for "HTLV-I, HTLV-II, HTLV-III and HIV, HIV1, HIV2, evoked potential, motor evoked potential, high voltage electrical stimulation, transcranial magnetic stimulation, magnetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The amplitude of the recorded signal is a function of the frequency and temporal coherence of the neural activity that controls that specific muscle [3]. Despite the usefulness of the abovementioned parameters in studying the function and dysfunction of the neural pathways at rest and during activity [4][5][6][7][8], the variability of the MEP elicited by TMS or the "M-jiggle" [9][10][11], defined as the variation of the size of the evoked potential from one stimulus to the next, has precluded its wider use in diverse settings.…”
mentioning
confidence: 99%
“…The amplitude of the recorded signal is a function of the frequency and temporal coherence of the neural activity that controls that specific muscle [3]. Despite the usefulness of the abovementioned parameters in studying the function and dysfunction of the neural pathways at rest and during activity [4][5][6][7][8], the variability of the MEP elicited by TMS or the "M-jiggle" [9][10][11], defined as the variation of the size of the evoked potential from one stimulus to the next, has precluded its wider use in diverse settings.…”
mentioning
confidence: 99%
“…The authors concluded that, in the retrovirusassociated neurodegenerative disorders, these differences in corticospinal tract involvement of patients with AIDS and HAM/TSP may help to orient early neurorehabilitation measures. 43 Nutritional/metabolic myelopathies Subacute combined degeneration (vitamin B12 deficiency). The neurological manifestations of vitamin B12 deficiency primarily result from the degeneration of the posterior and lateral columns of the spinal cord.…”
Section: Myelitismentioning
confidence: 99%